Clinical and pathological profile of Gallbladder Cancer (GBC) and Gallstone disease GSD) among the patients admitted in tertiary care institute in Kolkata - Abhishek Mohata; Mrinmoy Adhikary; Ranajit Bari; Shubho Chowdhuri; Pulak Kumar Jana; Vinoth Gnana Chellaiyan (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy, 2022)
Background: Gallstone disease (GSD) is one of the most common surgical problems throughout the world. The rise in gallstone disease burden and its wide spectrum of non-specific presentation makes the disease more challenging. Gall bladder cancer (GBC) is a common cancer in the northern and North-eastern States of India. The six cancer registries of the Indian Council of Medical Research (ICMR) (1990-1996) show a 10 times lower incidence of GBC per 1 00 000 in South India compared with the North. The objective of present study was to assess the epidemiological and pathological profile of GSD and GBC patients of Eastern India visiting tertiary care hospital of Kolkata.